Prevalence of psoriatic arthritis in Italy: insights from the multicentric MAPSI study - Serban, Teodora; Tramontano, Giuseppina; Pendolino, Monica; Roccatello, Dario; Epis, Oscar Massimiliano; Iannone, Florienzo; De Andres, Ilenia; Favero, Marta; Romeo, Nicoletta; Rovera, Guido; Santo, Leonardo; Tirri, Enrico; et al. (Frontiers in Medicine, 2025)
IntroductionPsoriatic arthritis (PsA) is a chronic inflammatory arthropathy associated with cutaneous psoriasis (PsO), first defined by Moll and Wright. Initially perceived as relatively benign, PsA is now recognized for its chronic, progressive, and destructive nature, significantly impacting patients' quality of life, similar to Rheumatoid Arthritis (RA). Globally, PsA represents about 20% of cases in early arthritis clinics, posing diagnostic and management challenges. Early diagnosis is crucial to prevent long-term disability and prevent comorbidities. While classification criteria for PsA are widely accepted, the lack of specific diagnostic criteria may delay diagnosis, with many patients experiencing delays of over a year before receiving an accurate diagnosis. For this reason, the exact prevalence of PsA remains uncertain.MethodsThe MAnagement of PSoriatic Arthritis in Italy (MAPSI) project is a multicenter observational study aimed to investigate the prevalence of PsA and characteristics in an Italian cohort. This study included 454 patients diagnosed or confirmed by a rheumatologist across 25 Rheumatology Units in Italy. Data were collected on demographics, clinical features, and treatment histories. In our cohort, distinct gender differences were observed in PsA phenotype and disease impact.ResultsMen had a higher prevalence of axial involvement and were more likely to be current or former smokers, while women showed greater rates of enthesitis and reported higher perceived disease activity. Additionally, women had a higher prevalence of psychological comorbidities, whereas men had more severe skin involvement; laboratory tests were often unhelpful in diagnosing PsA, with elevated inflammatory markers in only about half of the cases.DiscussionThese findings highlight the need for gender-sensitive approaches in the management of PsA. Our findings highlight the importance of comprehensive patient evaluation, including extramuscoloskeletal manifestation with a gender-sensitive approaches, focusing on a prompt diagnosis to prevent systemic comorbidities. Real-world data, such as those provided by the MAPSI study, are essential for understanding the burden of PsA and developing effective management strategies tailored to patient characteristics.